The conserved molecular determinants of virulence in dengue virus - Zuleeza A,; Poh, Chit Laa * (Ivyspring International Publisher, 2019)
Dengue virus belongs to the Flaviviridae family which also includes viruses such as the Zika, West Nile and yellow fever virus. Dengue virus generally causes mild disease, however, more severe forms of the dengue virus infection, dengue haemorrhagic fever (DHF) and dengue haemorrhagic fever with shock syndrome (DSS) can also occur, resulting in multiple organ failure and even death, especially in children. The only dengue vaccine available in the market, CYD-TDV offers limited coverage for vaccinees from 9-45 years of age and is only recommended for individuals with prior dengue exposure. A number of mutations that were shown to attenuate virulence of dengue virus in vitro and/or in vivo have been identified in the literature. The mutations which fall within the conserved regions of all four dengue serotypes are discussed. This review hopes to provide information leading to the construction of a live attenuated dengue vaccine that is suitable for all ages, irrespective of the infecting dengue serotype and prior dengue exposure.